Are NCAM deficient mice an animal model for schizophrenia? - Albrecht, Anne; Stork, Oliver (Frontiers in Behavioral Neuroscience, 2012)
Genetic and biomarker studies in patients have identified the Neural Cell Adhesion Molecule (NCAM) and its associated polysialic acid as a susceptibility factors for schizophrenia. NCAM and polysialtransferase mutant mice have been generated that may serve as animal models for this disorder and allow to investigate underlying neurodevelopmental alterations. Indeed, various schizophrenia-relevant morphological, cognitive and emotional deficits have been observed in these mutants. Here we studied social interaction and attention of NCAM null mutant (NCAM-/-) mice as further hallmarks of schizophrenia. Nest building, which is generally associated with social behavior in rodents, was severely impaired, as NCAM-/- mice continuously collected smaller amounts of nest building material than their wild type littermates and built nests of poorer quality. However, social approach tested in a three- compartment- box was not affected and latent inhibition of Pavlovian fear memory was not disturbed in NCAM-/- mice. Although NCAM deficient mice do not display a typical schizophrenia-like phenotype, they may be useful for studying specific endophenotypes with relevance to the disease.